The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/rmv.2416
|View full text |Cite
|
Sign up to set email alerts
|

Safety of varicella vaccination strategies: An overview of reviews

Abstract: The safety of new vaccines under development as well as existing vaccines is a key priority for national and international public health agencies. A number of countries have implemented universal childhood varicella vaccination programmes over the past 30 years. However, strategies differ in terms of the number of doses, type of vaccine(s) recommended, age at vaccination and interval between doses for a twodose schedule. An overview of reviews was undertaken to assess the existing systematic review evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Likewise, Hansen et al., 46 in a study of 14 042 children receiving DTaP‐IPV/Hib vaccines, found no increase in seizures or epilepsy. In addition to DTaP/IPV/Hib, there is no indication that the meningococcal, 47 MMR, 48,49 varicella, 49,50 influenza, 51 pneumococcal vaccine, 52 hepatitis A, 53 hepatitis B, 54 and HPV 55 vaccines cause epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Hansen et al., 46 in a study of 14 042 children receiving DTaP‐IPV/Hib vaccines, found no increase in seizures or epilepsy. In addition to DTaP/IPV/Hib, there is no indication that the meningococcal, 47 MMR, 48,49 varicella, 49,50 influenza, 51 pneumococcal vaccine, 52 hepatitis A, 53 hepatitis B, 54 and HPV 55 vaccines cause epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…A single search was conducted to retrieve systematic reviews on the efficacy, effectiveness and safety of alternative varicella vaccination strategies, with the latter outcome reported in a separate paper. 14 A comprehensive electronic search was performed in Embase (Elsevier), Medline (EBSCO), the Cochrane Library and Google Scholar on 2 February 2022, with databases searched since inception. The SYSVAC and PROSPERO registries were also searched to identify relevant reviews and registered protocols for forthcoming systematic reviews.…”
Section: Methodsmentioning
confidence: 99%